FACTORS INFLUENCING YOUTH PARTICIPATION IN AGRICULTURE IN WESTERN ZONE OF BAUCHI STATE, NIGERIA - Abdullahi, M.L.; Hassan, A.B.; Abdullahi, I.M. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the factors influencing youth participation in agriculture in the Western Zone of Bauchi State, Nigeria. A multistage sampling technique was employed to select 300 respondents. Data were collected through the administration of structured questionnaires and analyzed using descriptive statistics and binary logistic regression. Results revealed that the majority of youth participants are within the age bracket of 26-35 years with a mean 31 years, predominantly smallholder farmers managing farms of approximately 2.3 hectares, with a monthly income averaging ₦48,900. Crop production emerged as the major occupation (79.05%) while 51.35% and 38.18% were engaged in rearing livestock and agro-processing. The results of regression analysis revealed that age, marital status, education level, household size, farming experience, membership in associations, extension contact, access to credit, farm size, use of agro-chemicals, and labor type were significant (P<0.05) in influencing youths participation in agriculture. The major constraints to youth participation in agriculture were limited access to credit (mean = 4.48), high input costs (mean = 4.23), and inadequate land access (mean = 4.06). The study concluded that age, marital status, education level, household size, farming experience, membership in associations, extension contact, access to credit, farm size, use of agro-chemicals, and labor type were the factors influencing youth participation in agriculture in the study area. The study recommends the need for government and development partners to address financial, land, infrastructural, and security challenges, alongside promoting capacity building with the aim of enhancing youth engagement in agriculture.